2009
DOI: 10.1143/jjap.48.031103
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Fabrication Process for ZnO Thin-Film Transistors with HfO2 Gate Dielectrics

Abstract: We report measurements of the thermal conductivity, specific heat, and critical temperature of the aluminium alloy 5056 in the range 0.05 to 1.3 K. The absence of magnetic anomalies in the specific heat and the rather high thermal conductivity in the superconducting state would allow reasonably fast cool-down below 0.1 K of multiton gravitational wave antennae made of this material. On the basis of the measured properties. the desired refrigerator characteristics are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…22 Also, in our previous study, 12 the threshold voltage degradation of the ZTO TFT followed the stretched exponential behavior. Figure 5 shows that the time dependence of V th can be well fitted with the stretched-exponential equation.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…22 Also, in our previous study, 12 the threshold voltage degradation of the ZTO TFT followed the stretched exponential behavior. Figure 5 shows that the time dependence of V th can be well fitted with the stretched-exponential equation.…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, it is found in our work that there exists an interaction between HfO y and ZTO, therefore, having AlO x on top of HfO y reduces the interaction with ZTO and thus high mobility as well as stable performance can be achieved. Besides, it is found that Zn can diffuse easily into HfO y , 22 have a role of Zn diffusion barrier. This leads to an enhancement of TFT performance.…”
Section: Resultsmentioning
confidence: 99%
“…High-k gate insulators can offer high capacitance and low leakage current density, so the use of high-k gate insulators is the optimum approach [4]. So far, various high-k gate dielectrics, including Bi 1.5 Zn 1.0 Nb 1.5 O 7 (BZN) [5][6][7][8][9], HfO 2 [10,11], and SiN x [12,13] etc., have been extensively researched because of low leakage current density and high permittivity. Among of those high-k gate insulators, BZN thin films have shown the best performance due to the formation of the partial nanocrystalline BZN phase in the amorphous matrix [14].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-based thin film transistors ͑TFTs͒ [1][2][3][4][5][6][7][8][9][10][11][12][13][14] have been studied extensively in recent years owing to their potential for replacing hydrogenated amorphous or polycrystalline silicon ͑poly-Si͒ TFTs. In addition to the high mobility ͑comparable to that of poly-Si TFTs͒, these ZnO devices do not require prolonged high temperature annealing for dopant activation.…”
mentioning
confidence: 99%
“…This important feature provides faster throughput enhancement and greater energy savings during production. Moreover, ZnO is transparent to visible light and allows low temperature manufacturing; the former advantage especially may assist in the realization of a next generation transparent TFT backplane, [2][3][4][5][6][12][13][14] and if the high quality of the gate dielectric is also available simultaneously in a low temperature process, the latter advantage may assist in the fabrication of flexible electronics. 15 Although many benefits exist for the ZnO TFT, for further applications involving high speed and low power integrated circuits, the TFTs must possess a low threshold voltage and a small subthreshold swing ͑SS͒.…”
mentioning
confidence: 99%